Representation of an identity and a culture through the imagination of Rabah Belamri’s childhood - GUEBBAS, Abla (Journal of Human Sciences, 2021)
The roots of the community always remain buried in the memories of the imaginary and in the identity, which allows the individual to ensure the reconstruction of his self. Literature, defined by Aristotle as a mimesis, will come to immortalize many of these realities and a writing will come to faithfully represent societies by introducing repressions and memories. While accessing the depths of himself and going beyond pure description, Rabah Belamri will apply himself to writing himself. He explores his childhood and brings it back to us as he lived it. He would have indulged in self-therapy by digging into his subconscious to rebuild a depth of his being. Thus, this line of thought will focus on the "Representation of identity and culture through the imagination of Rabah Belamri’s childhood". To do this, Freudian theories will support this problematic and the two works L’Asile de Pierre and Femmes sans Visage, in which we see the author’s experience, will serve as a corpus.